Metaphor Reality Group Counseling Techniques to Increase Self-Esteem Students with Nomophobia Symptoms (Jurnal Bimbingan Konseling, 2020)
This study aims to analyze the effectiveness of Metaphorical Reality group counseling to improve self-esteem in vocational students with nomophobic symptoms. This study used a Pretest-Posttest Random Control Group design involving 14 students selected by purposive sampling grouped into two randomly 7 people for each group. Data collection was performed using the Rosenberg Self-Esteem Scale (RSES) and Nomophobia Questionnaire (NMP-Q). Mann-Withney U and Wilcoxon test results showed that the metaphorical reality engineering intervention group increased self-esteem in students with nomophobic symptoms, Z = -2.375, p < 0.05. This finding proves that metaphorical group reality counseling is effective for increasing self-esteem in students who experience symptoms of nomophobia.